2004
DOI: 10.1177/0363546503261421
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Specific High-Intensity Training Sessions on Football Referees’ Fitness Levels

Abstract: As match officials are subjected to a high physical load during matches, they should follow structured weekly training plans that have an emphasis on intensive, intermittent training sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
33

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 16 publications
5
56
0
33
Order By: Relevance
“…Moreover, Weston et al (31) did not observe differences between referees and players for the total distance covered in a game, high-intensity running and sprints. These similarities in actions in a game between referees and players corroborate the idea that soccer referees should be more professionally and specifically physically fit (6,32) .…”
Section: Movement Profile Of the Soccer Referees In Official Gamessupporting
confidence: 60%
See 3 more Smart Citations
“…Moreover, Weston et al (31) did not observe differences between referees and players for the total distance covered in a game, high-intensity running and sprints. These similarities in actions in a game between referees and players corroborate the idea that soccer referees should be more professionally and specifically physically fit (6,32) .…”
Section: Movement Profile Of the Soccer Referees In Official Gamessupporting
confidence: 60%
“…The use of this test letus verify the increase of aerobic and anaerobic fitness ofthe referee. According to Weston et al (6) , after a physical training program with high intensity exercise sessions, the YoYo intermittent recovery testwas more sensitive to measure the anaerobic fitness increase-the same observation made by Krustrup and Bangsbo (40) .…”
Section: Critical Analysismentioning
confidence: 70%
See 2 more Smart Citations
“…Talanian et al 9 have also found that an intermittent sprinting exercise program significantly elevated aerobic power; in this study, the oxidative enzyme b-hydroxyacyl-CoA dehydrogenase was used as an indicant of mitochondrial volume and was found to increase by 31%, suggesting that intermittent sprinting enhances mitochondrial capacity. Other studies have also shown increases in aerobic power to differing forms of intermittent sprinting, [21][22][23] whereas Tabata et al 23 found that intermittent sprinting also resulted in significant increases in anaerobic capacity. Collectively, these data show that intermittent sprinting results in significant improvements in both aerobic and anaerobic fitness.…”
Section: Discussionmentioning
confidence: 96%